Penyelesaian Soal-Soal Mengerti Fisika : Mekanika, Termofisika, Listrik dan Magnet, Gelombang - HIEN, Kian Tan (Andi Offset, 1993)
Penyelesaian Soal-Soal Mengerti Fisika : Mekanika, Termofisika, Listrik dan Magnet, Gelombang